Senescence Back and Forth - Nydegger, Urs.; Lung, Thomas (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book is about lifelong ageing of humans. The basic biochemical and genetic mechanisms remain ill known, and differ among individuals. The book starts out to explore the plant and animal kingdoms to answer questions human ageing needs for understanding. First, we come to scrutinize time running out and what 'normal' means with impacts on the genome and on protein half- lives and function. Ageing goes beyond biochemical skid treated by geroprotector drugs, including biosimilars; albeit early diagnosis with standard medical laboratory assays, here addressed, sheds light with focus on basic research. Modern tools, including machine learning, and DNA technology, e.g. genomics, have already provided for unanticipated insights. The chapters then turn around senescence of the entire organism based on variable ageing of single organs embedded in neuronal networks . Psychological stress factors, dementia opposed to vigilance, and distinction of ageing from overt disease arecontrasting in humans and are opposed in the book. Senescence, seen as a one way track may be reverted into rejuvenation, made possible by insights into immunosenescence and genomic approaches. Risk management in health insurance finds important clues in this book. The topics addressed between the book covers help to understand the trend to the ever- prolonging life expectancy beyond the centenarian age group; nursing care takers and pharmaceutical industry are invited to understand what' is going on in senior people to make their geriatric population remain fit or become frail.
Senescence opposed to longevity -- Genetics, the language of Proteomics -- Plants Uncover Senescence Animals Way Off Humans -- Rejuvenation stops Senescence -- Overlap of Senescence with Disease -- Mosaic Restricted to the Individuum -- Remaining Time until Death -- Laboratory Checkups -- eroprotectors.
Keywords: Aging; Medicine -- Research; Biology -- Research; Public health; Biotechnology; Psychiatry; Ageing; Biomedical Research; Public Health; Chemical Bioengineering; Psychiatry